2012
DOI: 10.5402/2012/851831
|View full text |Cite
|
Sign up to set email alerts
|

Rhinosinusitis in Children

Abstract: Rhinosinusitis is the inflammation of the mucous membranes of nose and paranasal sinus(es). 5–13% of upper respiratory tract infections in children complicate into acute rhinosinusitis. Though not life threatening, it profoundly affects child's school performance and sleep pattern. If untreated, it could progress to chronic rhinosinusitis (CRS). The pathogens involved in perpetuation of CRS consist of multidrug-resistant mixed microflora. CRS is challenging to manage and could further extend to cause eye or in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 134 publications
0
6
0
Order By: Relevance
“…52 Rhinosinusitis is an upper airway infection with chronic implications and prompt management of acute cases would prevent cases from slipping into chronicity with resistant polymicrobial infections. Management of CRS is an expensive, long-term affair with high likelihood of complications.…”
Section: Asthma and Crs In The Pediatric Populationmentioning
confidence: 99%
See 2 more Smart Citations
“…52 Rhinosinusitis is an upper airway infection with chronic implications and prompt management of acute cases would prevent cases from slipping into chronicity with resistant polymicrobial infections. Management of CRS is an expensive, long-term affair with high likelihood of complications.…”
Section: Asthma and Crs In The Pediatric Populationmentioning
confidence: 99%
“…Achieving sinonasal eutrophism and efficient mucociliary transport is important to sinus health and reduction of recurrences. 52 …”
Section: Asthma and Crs In The Pediatric Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…Eumycetoma is caused primarily by Madurella mycetomatis , but the aetiological agents of this disease vary with geographical regions [9] . In the tropics, Curvularia species are significant causes of fungal keratitis associated with trauma from fungus-contaminated plant materials [12] , [13] while the Bipolaris , Curvularia , Exserohilum , Alternaria and Drechslera are frequently reported to be involved in invasive sinusitis [14] [17] . Systemic dematiaceous fungal infections are rare compared to systemic candidiasis and aspergillosis.…”
Section: Introductionmentioning
confidence: 99%
“…Sinus opacification, air-fluid level, and increased mucus thickness are considered to be positive radiological evidences of sinusitis. Various studies have shown moderate sensitivity and specificity of X-rays in diagnosing sinusitis in children and have also noted that the inability of radiography to differentiate among inflammation, infection, and tumour is an important problem in this diagnostic modality ( 10 12 ).…”
Section: Introductionmentioning
confidence: 99%